2022
DOI: 10.3389/fmicb.2022.902996
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated With Soil Prevalence of the Melioidosis Pathogen Burkholderia pseudomallei: A Longitudinal Seasonal Study From South West India

Abstract: Melioidosis is a seasonal infectious disease in tropical and subtropical areas caused by the soil bacterium Burkholderia pseudomallei. In many parts of the world, including South West India, most cases of human infections are reported during times of heavy rainfall, but the underlying causes of this phenomenon are not fully understood. India is among the countries with the highest predicted melioidosis burden globally, but there is very little information on the environmental distribution of B. pseudomallei an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…The disease is endemic to southeast Asia and northern Australia (1) and is also one of the emerging infections in India, where it is more concentrated in its subtropical, wetter, and peninsular parts while the drier, north-western part is relatively spared (2)(4). Unfortunately, due to a lack of awareness and poor suspicion, the diagnosis of melioidosis is often delayed or overlooked (3). Burkholderia pseudomallei can be found ubiquitously in soil, muddy water from irrigated elds, and animal excreta.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is endemic to southeast Asia and northern Australia (1) and is also one of the emerging infections in India, where it is more concentrated in its subtropical, wetter, and peninsular parts while the drier, north-western part is relatively spared (2)(4). Unfortunately, due to a lack of awareness and poor suspicion, the diagnosis of melioidosis is often delayed or overlooked (3). Burkholderia pseudomallei can be found ubiquitously in soil, muddy water from irrigated elds, and animal excreta.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular detection does not necessarily indicate the presence of viable and culturable bacteria, the high discrepancy between molecular and culture-based B. pseudomallei detection rates points to a remarkable lack of sensitivity of commonly applied culture methods. Moreover, the fact, that culture-based environmental screenings in regions of high melioidosis endemicity have resulted in either no or only very few culture-positive samples ( Benoit et al, 2015 ; Wiersinga et al, 2015 ; Shaw et al, 2022 ), further indicates a potential sensitivity problem of the available culture methods used in those studies, including the currently recommended consensus method using TBSS-C50 ( Limmathurotsakul et al, 2013 ). We recently accomplished a significant improvement in the isolation rate of B. pseudomallei from rice paddy soil samples by introducing TBSS-C50-based erythritol medium in which erythritol is the sole carbon source ( Trinh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Informative case series have been published from Tamil Nadu [18], Kerala [19] and Karnataka [20] in southern India and Odissa in eastern India [21]. An extensive soil sampling study from southwest India showed the wide environmental distribution of B. pseudomallei but with considerable differences in abundance between sites and within single sites, the highest abundance during the rainy season and the presence of B. pseudomallei linked to nutrient-depleted habitats [22 ▪ ].…”
Section: Epidemiologymentioning
confidence: 99%